Coaching GROW, Mentoring, and Teacher Professional Development in Madrasah Ibtidaiyah: A Case Study - Shinta Meirnawati Pratiwi Putri; Mulyawan Safwandy Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of GROW model coaching, competency-based mentoring, and teacher professional development programs in improving the quality of learning at Madrasah Ibtidaiyah Matla’ul Atfal. The study employed a qualitative approach with a case study design. The research participants consisted of 1 principal, 4 senior teachers serving as mentors, 12 teachers, and 1 madrasah supervisor. Data were collected through in-depth interviews, observations, and the analysis of 15 documents, including supervision programs, professional development reports, lesson plans, and evaluation records. Data validity was ensured through source, technique, and time triangulation. Data were analyzed using thematic analysis through a systematic coding process. The findings reveal that the GROW coaching model effectively enhances teachers’ professional reflection, competency-based mentoring strengthens pedagogical practices, and professional development programs, such as workshops, in-house training (IHT), and coaching clinics, foster a sustainable culture of teacher learning. The main challenges identified include limited time, administrative workload, and a weak evaluation system. This study proposes an integrated practice-based supervision and professional development model and provides strategic recommendations for improving the quality of learning in madrasah settings.